1996
DOI: 10.1111/j.1469-8137.1996.tb01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble N compounds in trees exposed to high loads of N: a comparison of spruce (Picea abies) and beech (Fagus sylvatica) grown under field conditions

Abstract: summary During the vegetation period 1994, the nitrogen (N) composition and contents of leaves, xylem sap and phloem exudates of twigs from a coniferous (Picea abies (L.) and a deciduous (Fagus sylvatica L.) tree species were analysed at a field site (Höglwald, Germany) exposed to high loads of N. In April, total soluble non‐protein N (TSNN) in the xylem sap of twigs from spruce and beech reached a maximum of about 7.0 and 15.0 μmol ml−1, respectively, probably owing to remobilization of stored N. After bud br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
153
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 139 publications
(170 citation statements)
references
References 47 publications
17
153
0
Order By: Relevance
“…A totally different situation was observed for beech which showed a seasonal maximum of TSNN in the root xylem and phloem before\during bud break with a subsequent decrease. A seasonal course of N contents similar to that in beech roots has previously been observed in above-ground parts of beech and spruce trees, with maximum N transport in xylem (Glavac & Jochheim, 1993 ;Dambrine et al, 1995 ;Schneider et al, 1996) and phloem immediately before and during bud break. The N supply of newly developing tissues of trees during spring can at least partly be met by remobilization of internal N sources from storage tissues (Millard & Proe, 1992 ;Millard, 1994).…”
Section: Differences In Tsnn Contents In Beech and Spruce In Spring Mmentioning
confidence: 82%
“…A totally different situation was observed for beech which showed a seasonal maximum of TSNN in the root xylem and phloem before\during bud break with a subsequent decrease. A seasonal course of N contents similar to that in beech roots has previously been observed in above-ground parts of beech and spruce trees, with maximum N transport in xylem (Glavac & Jochheim, 1993 ;Dambrine et al, 1995 ;Schneider et al, 1996) and phloem immediately before and during bud break. The N supply of newly developing tissues of trees during spring can at least partly be met by remobilization of internal N sources from storage tissues (Millard & Proe, 1992 ;Millard, 1994).…”
Section: Differences In Tsnn Contents In Beech and Spruce In Spring Mmentioning
confidence: 82%
“…The exuding xylem sap was collected in Eppendorf caps, frozen under liquid nitrogen, and stored until analysis at Ϫ80°C. Contamination with cellular compounds was measured by ATP analysis as described by Schneider et al (1996) and was less than 1%, as previously reported for other plant species.…”
Section: Xylem Sap Samplingmentioning
confidence: 99%
“…Organic material transported with the phloem flow was extracted by phloem exudation technique as described by Schneider et al (1996) and Gessler et al (2004).…”
Section: Extraction Of Phloem Soluble Sugarsmentioning
confidence: 99%